Preventive Effect of Gonggan (Citrus Reticulata Blanco Var. Gonggan) Peel Extract on Ethanol/HCl-Induced Gastric Injury in Mice via an Anti-oxidative Mechanism - Wu, Ya; Jiang, Hua; Chen, Guangfang; Chen, Xingxing; Hu, Chengming; Su, Xiaofei; Tan, Fang; Zhao, Xin (Frontiers in Pharmacology, 2021)
Gonggan (Citrus reticulata Blanco var. gonggan) is one of the most popular citruses. In this study, the effect of Gonggan peel extract (GPE) on gastric injury induced by ethanol/hydrochloric acid was investigated. HPLC result showed GPE mainly contained the flavonoids narirutin, hesperidin, nobiletin, tangeretin and 5-demethylnobiletin. Morphological and pathological analysis of gastric tissue revealed that GPE could relieve gastric injury. Also, GPE increased the levels of SOD, GSH-Px, and CAT and decreased the level of MDA. Moreover, GPE decreased the levels of the inflammatory cytokines TNF-α, IFN-γ, IL-1β, and IL-6 to suppress inflammation. In addition, the q-PCR results showed that GPE upregulated the mRNA expression of SOD1, SOD2, 𝛾-GCS, GSH-Px, CAT, and IκBα and downregulated the mRNA expression of NF-κB conclusion, GPE alleviated gastric injury caused by ethanol/hydrochloric acid by inhibiting oxidative stress and the inflammatory response. The mechanism by which GPE protects gastric tissues may involve the antioxidative pathway. Therefore, GPE has great potential to be developed as a product to prevent gastric injury.